The Value of a Diamond: Understanding Global Coverage of Diamond Open Access Journals in Web of Science, Scopus, and OpenAlex to Support an Open Future - Simard, Marc-André; Basson, Isabel; Hare, Madelaine; Larivière, Vincent; Mongeon, Philippe (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2024)
Diamond OA journals present a publishing model that is free for both authors and readers, but their lack of indexing in major bibliographic databases such as Web of Science (WoS) and Scopus presents challenges in assessing the usage of these journals. This paper provides a global picture of the coverage of diamond OA journals from the Directory of Open Access Journals (DOAJ) in three data sources. Results show their low coverage in WoS and Scopus and higher coverage in OpenAlex, as well as the generally smaller and local scope of diamond OA journals. Understanding the current landscape of diamond OA indexing can assist LIS professionals with advising researchers on avenues they can pursue to find diamond OA published work or choosing journals to publish in to ensure the visibility and accessibility of their research.